Otolaryngology Education in the Setting of COVID-19: Current and Future Implications. (July 2020) - Comer, Brett T.; Gupta, Nikita; Mowry, Sarah E.; Malekzadeh, Sonya
The COVID-19 pandemic continues to garner extensive international attention. The pandemic has resulted in significant changes in clinical practice for otolaryngologists in the United States; many changes have been implemented to mitigate risks identified by otolaryngologists in other countries. COVID-19–induced limitations include social distancing and triaging of patient acuity. Additionally, a recent publication by Stanford University has drawn attention to the risks that otolaryngologists may face with regard to manipulation of the upper airway and mucosal disruption. As a result of COVID-19 recommendations, multiple institutions have overhauled resident clinical rotations and resident education. The result has been a rapid and significant change in resident education at most academic institutions. This commentary outlines the development of the otolaryngology resident education consortiums, with implications for future education within and outside of otolaryngology.